2022
DOI: 10.3389/frobt.2022.1011327
|View full text |Cite
|
Sign up to set email alerts
|

Finding ikigai: How robots can support meaning in later life

Abstract: Previous research in human-robot interaction has explored using robots to increase objective and hedonic aspects of well-being and quality of life, but there is no literature on how robots might be used to support eudaimonic aspects of well-being (such as meaning in life). A sense of meaning has been shown to positively affect health and longevity. We frame our study around the Japanese concept of ikigai, which is widely used with Japanese older adults to enhance their everyday lives, and is closely related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…This also suggests that the use of robots in the home might be particularly appropriate for supporting ikigai in ways that are currently not available to OAs. These findings add to our previous survey-based study of OAs in the United States, conducted as part of this same broader project on developing robots to support OAs’ ikigai, which found that OAs often obtain ikigai by helping others, through family connections, and/or through activities of daily life, that sources of meaning often differ based on the OAs’ living situation, and that OAs are generally positive about the potential of using social robots to assist in supporting meaning in later life [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…This also suggests that the use of robots in the home might be particularly appropriate for supporting ikigai in ways that are currently not available to OAs. These findings add to our previous survey-based study of OAs in the United States, conducted as part of this same broader project on developing robots to support OAs’ ikigai, which found that OAs often obtain ikigai by helping others, through family connections, and/or through activities of daily life, that sources of meaning often differ based on the OAs’ living situation, and that OAs are generally positive about the potential of using social robots to assist in supporting meaning in later life [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified age-specific strategies for interacting with conversational agents [25]. For older adults, companion robots can evoke feelings of independence and empowerment [26].…”
Section: Socially Assistive Robots In Elderly Carementioning
confidence: 99%
“…In addition, we analyze how an “ikigai” robot—showcased to participants via video—is viewed by older adults and might further be developed to support their ikigai. Previous studies with older adults in the United States have suggested that robots may be beneficial in helping older adults maintain and enhance their ikigai [ 20 ]. In addition, feedback obtained via interviews with ikigai experts, both academic scholars and those running ikigai centers in Japan, has been largely positive about the idea of using robots cross-culturally to support ikigai [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ikigai-9 is a 9-item scale developed with Japanese older adults aged >60 years, designed as a tool to measure their sense of ikigai across three different aspects: (1) optimistic and positive emotions toward life (eg, “I often feel that I am happy”), (2) active and positive attitudes toward one’s future (eg, “I would like to learn something new or start something”), and (3) acknowledgment of the meaning of one’s existence (eg, “I believe that I have some impact on someone”) [ 28 , 43 ]. The reliability of both scales has been validated with Japanese populations [ 43 , 44 ] (and international populations for the kigai-9 [ 28 ]), and they have been used as valid tools to investigate older adults’ ikigai [ 20 , 28 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation